Systems and Operations of the Ghana Science-Policy Dialogue Platform on Climate Change, Agriculture and Food Security - Botchway, Vincent Ansah; Sam, Kingsley Odum; Karbo, Naaminong; Essegbey, George Owusu; Nutsukpo, Delali; Agyemang, Kingsley; Zougmoré, Robert B.; Partey, Samuel T. (Council for Scientific and Industrial Research, Ghana, 2016)
The threat posed by climate change and its variability within sub-Saharan Africa especially West Africa is compounded by its weak economies and high dependence on Agriculture as a major driver of economic growth. Ghana has since 2010 undertaken several initiatives towards development of comprehensive programmes (strategies) to enhance national adaptation to climate change. Diverse governmental and academic/research institutions, private sector and individuals have initiated programmes and projects aimed at delivering on CSA to enhance livelihoods, increased agricultural production and sustainable socio-economic development. However, the activities of these stakeholders in the climate change arena appeared isolated, disjointed and uncoordinated to reap desired benefits. In response, the CCAFS programme in West Africa coordinated by ICRISAT, Bamako involving Ghana, Mali and Senegal was able to set up national multi-stakeholder platforms for information sharing and learning on climate change and related policy issues. The Ghana CCAFS Science-Policy Dialogue Platform having been operational since November 2012 has wealth of experiences to share. This note is therefore designed to highlight the profile of Ghana’s platform, its structure and composition and the key achievements over the past 4-5 years of existence.